Efficacy of various survey methods to detect an experimental population of spot-tailed earless lizards: A case study - Evan Drake Rangel; Scott E. Henke; David B. Wester; Gabriel Andrade-Ponce; Ruby A. Ayala; Cord B. Eversole (PLoS ONE, 2025)
Plateau ( Holbrookia lacerata ) and Tamaulipan ( Holbrookia subcaudalis ) spot-tailed earless lizard (STEL) populations have experienced declines in population size and distribution. Both species are considered species of concern and Tamaulipan STEL are being considered for federal threatened status. Even with this heightened concern, little is known about these species. Therefore, our objectives were to determine the most effective and time-efficient methods to survey for STEL, and to determine if a lizard density threshold was required before STEL presence could be detected. We evaluated ten standard reptile search techniques (i.e., pitfall traps, funnel traps, two thermoregulation lures (i.e., rock mounds and cover boards), remote camera surveys, detection dog surveys, quadrant searches, systematic visual searches, environmental DNA sampling, and road cruising) to identify STEL relative abundance within a 1 ha enclosure. The 1 ha enclosure was divided into 100, 10 x 10 m quadrants and each reptile search technique was replicated five times and randomly assigned to a quadrant without replacement. STEL were randomly placed inside the enclosure at known densities of 5, 10, 20, 30, and 40 lizards per ha and their relative abundance was assessed by each method three times at each STEL density during August – September, 2021. STEL were allowed 6-day acclimation periods before increasing density. Because STEL were translocated to novel habitat, caution in interpretation should be noted. However, STEL were not detected using funnel traps, rock mounds, cover boards, remote cameras, and detector dogs at any density level. Pitfall traps, quadrant searches, and eDNA samples detected few STEL, but only at 40 STEL/ha density. Only systematic visual searches and road cruising yielded STEL detections at multiple densities; however, neither method could reliably predict STEL density. Because our detection rates were low (~7% at any STEL density), road cruising can be more time efficient to survey a larger area. Once locations with STEL have been identified, then systematic visual searches between 1300–1500 hr can be conducted to determine the relative abundance of these elusive species.